Introduction - Węc, Klaudia Izabela (Studia Paedagogica Ignatiana, 2021)
Art therapy has become one of the most dynamically developing forms of working with a person. We may assume that the reasons for such interest in art therapy include the change in thinking about a human being and increasingly complex challenges they had not have to face before. There is no doubt that the complexity of human existence, along with its uncertainty and changeability, reveals the need to find the meanings that make it possible to rest from everyday life or receive support in difficult moments. Also, we are getting more and more aware of the fact that contact with art increases a person’s developmental potential, both in terms of their intellectual resources and creative abilities. Therefore, we may say that art therapy makes it possible for us to fully experience our own existence and to cope with the challenges of the contemporary world.